Avaliação do teste químico no diagnóstico de intolerância à lactose e sua associação com polimorfismo genético em uma população de Fortaleza/Ce - Ponte, Paulo Roberto Lins (2012)
Intolerance to lactose is a clinical syndrome comprising one or more corteges symptomatology associated with the ingestion of milk (clinical phenotype intolerant) and lactose tolerance in the absence of symptoms (clinical phenotype tolerant). Thus, in practice, must be attentive to cases similar to these badly absorptive symptoms because the convergences and differences between these disorders are tenuous and diagnoses are often inaccurate, making treatment and unsatisfactory conduct. Therefore, studies are needed using different diagnostic methods, and compare the different methods used in clinical practice and determine the most appropriate to give a conclusive diagnosis, since it is not always easy, given that the symptoms suggest other diseases. Objective.To evaluate the phenotypic characteristics, the response to chemical test for lactose tolerance and the genotype of patients with diagnostic hypothesis of intolerance to lactose and the correlation between them.Material and methods. We conducted a cross-sectional study at the University Hospital Walter Cantidio (HUWC), with 173 patients who had positive phenotype and were seen at the outpatient service of servers HUWC, from January to August 2010. The final sample consisted of 119 patients who underwent the lactose tolerance test and genotyping of the gene for lactase-phlorizin hydrolase (LPH). Results. Among the participants, most were: female, 54.6% (65 cases), the age group of 46-55 years old, 26.5% (32 cases); married, 65.6% (78 cases); dun-colored, 53.8% (65 cases); higher level, 42.9% (51 cases). The prevalence of intolerance to lactose was 45.4% and chemical intolerance was 73.9%. Symptoms investigated more prevalent in lactose intolerant were flatulence 81.4% (44 cases); bloating, 68.5% (37casos); borborygmus, 59.3% (32 cases) and diarrhea, 46, 3% (25 cases). The presence of the polymorphisms C> T polymorphisms and 13 910-G> A-22018 in LPH gene was identified in individuals selfreferred as lactose intolerant, and is therefore an excellent test for the diagnosis. The diagnosis of lactose intolerance that most had adequate baseline the difference was <15 with ROC curve greater than 80.3%, with good sensitivity and specificity. Conclusions. There is a correlation between genotype and chemical intolerant individuals, suggesting that the molecular test could be proposed for the laboratory diagnosis of lactose intolerance, and the chemical test, the difference basal <15 was more appropriate.